Bio-Based Solutions for Concrete Infrastructure: A Review of Microbial-Induced Carbonate Precipitation in Crack Healing - Armstrong Ighodalo Omoregie; Chih Siong Wong; Adharsh Rajasekar; Jen Hua Ling; Abdelfatah Bousbia Laiche; Hazlami Fikri Basri; Gowthaman Sivakumar; Tariq Ouahbi (Buildings)
Microbial-induced carbonate precipitation (MICP) is gaining attention as an eco-friendly and sustainable method for concrete crack repair. However, key challenges related to its large-scale implementation, regulatory approval, and integration into existing construction standards remain underexplored. This review examines recent advances in MICP, emphasizing its role in circular economy practices and sustainable building solutions. Traditional synthetic sealants contribute to environmental pollution and have limited long-term durability, highlighting the need for greener alternatives. Global research trends reveal an increasing focus on self-healing materials, biomineralization, and durability enhancement, alongside emerging innovations such as encapsulation technologies, marine applications, and bio-based composites. Unlike previous reviews, this study integrates bibliometric analysis to systematically assess research trends, identify key collaboration networks, and evaluate regulatory challenges that impact MICP adoption. While MICP offers significant advantages, including self-healing capabilities and compatibility with industrial by-products, barriers related to cost, scalability, and policy integration persist. This review identifies critical thematic clusters which include microbial action, sustainability, and engineering applications. This helps to provide actionable insights for researchers, engineers, and policymakers. By fostering interdisciplinary collaboration, MICP has the potential to become a transformative solution for resilient and environmentally sustainable infrastructure.